Biosorption study of methylene blues dyes using e.spinosum : interaction study between pH, initial concentration and dosage - Nor Hasyimah, Sudin (2018)
Removal of dyes from the industries has growing interest among the researchers in developing low cost and high efficiency technologies. Biosorption that using marine algae has become the ideal alternative for removing the dyes in aqueous solution. The study is aimed to the interaction of parameters and optimum conditions. The operating parameters that involved are biomass dosage (0.1-3g/L), initial concentration (5-150mg/L) and pH (2-12). The biosorption performance was determined by conducting the batch biosorption experiments. The results indicate as the biomass dosage increasing the percentage of removal also increasing. The variety of pH do not give a large effect to the biosorption process. From the experiment data, its show that the initial concentration is at 5mg/L and the optimum dosage is at pH 6. The maximum removal percentage for interaction between biomass dosage and initial concentration is 95% at concentration 150mg/L. Meanwhile, for the interaction between pH and biomass dosage, the maximum removal percentage is 86% at pH 6.